A Review on the Relationship between Matrix Metalloproteinases (Mmps) and their Natural Inhibitors (Tissue Inhibitors Of Matrix Metalloproteinases [Timps]) and the Success of an Autologous Arteriovenous Fistula (Avf) - Abdul Rahman, Mohd Norhisham Azmi; Othman, Ahmad Faidzal (IIUM Medical Journal Malaysia, 2021)
Since its introduction by Brescia and Cimino in 1966, arteriovenous fistula has been regarded as the best vascular access for haemodialysis purpose. However, it’s not without any drawbacks which has cost over USD1 billion in the United States alone to rectify them. Intimal hyperplasia has been shown to be a major contributory factor to this development. Intimal hyperplasia is a complex molecular process resulting in unwarranted accumulation of contractile smooth muscle cells, myofibroblasts, fibroblasts, and macrophages. There is an increasing amount of evidence suggesting that matrix metalloproteinases (MMPs) and its natural inhibitors (tissue inhibitors of matrix metalloproteinases ([TIMPs]) play a pivotal role in the development of intimal hyperplasia. Our purpose of writing this review article is to examine these evidences and to suggest of what future research questions need to be answered to further strengthen and clarify this relationship.